2017
DOI: 10.3329/bjvm.v15i1.34058
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of Clinical Diseases and Conditions of Pet Animals at Chittagong City Area, Bangladesh

Abstract: This study was conducted to estimate the proportional prevalence of clinical diseases and conditions in pet animals (dog, cat, and rabbit) attended at S. A. Quaderi Teaching Veterinary Hospital, Chittagong Veterinary and Animal Sciences University (CVASU), Chittagong, Bangladesh. A total of 388 cases of different clinical diseases and conditions were recorded during the study period from October 2016 to January 2017. Among them the overall proportional prevalence of clinical diseases and conditions in dog, cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Mange, lacerated wound, and abortion had a significant (p < 0.05) breed wise variation in terms of proportional incidence, and these diseases occurred more in local breed than other breeds. Yadav et al (2017) also reported that the occurrence of mange was greater in local breed than other exotic breeds, which supported the findings of the present study. The existing findings might be due to exotic breeds were mostly reared with proper care, but the local breeds did not get such intensive care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mange, lacerated wound, and abortion had a significant (p < 0.05) breed wise variation in terms of proportional incidence, and these diseases occurred more in local breed than other breeds. Yadav et al (2017) also reported that the occurrence of mange was greater in local breed than other exotic breeds, which supported the findings of the present study. The existing findings might be due to exotic breeds were mostly reared with proper care, but the local breeds did not get such intensive care.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the gender wise distribution of diseases, the proportional incidence in male dogs was higher than that in female dogs, which conformed the findings of Yadav et al (2017) in the Chittagong city of Bangladesh and Behera et al (2015) in Odisha, India. According to this study, female was more prone to gastroenteritis than male, showing a contradiction with the findings of Ide et al (2002) who found male suffers more from gastroenteritis than female due to higher oxidative GS-German Sheperd; LR-Labrador Retriever; GR-Golden Retriever; D-Doberman; P-Pomeranian; L-Local breed.…”
Section: Discussionsupporting
confidence: 82%
“…Out of all the disease categories, viral diseases were the most common in both males and females (p<0.05); nevertheless, males were more likely than females to have viral diseases (Table 2). The results of Yadav et al (2017), who found that male dogs had a greater illness prevalence than female dogs (58.72% vs 41.28%), corroborated this finding. According to this research, sex significantly affects the relationship between illness and pet dogs.…”
Section: Prevalence Of Clinical Diseases Of Pet Dogs At Cvhmentioning
confidence: 61%
“…Consequently, it is necessary to look into diseases in dogs, particularly in Dhaka, due to the presence of a large number of pet population. While studies on the clinical diseases in pets have been conducted in various parts of Bangladesh (Tarafder and Samad, 2010;Mahmud et al, 2014;Parvez et al, 2014;Yadav et al, 2017;Hasib et al, 2020;Hossain et al, 2022), there is comparatively little information available regarding the prevalence and associated risk factors of these conditions in dogs in Dhaka city. Furthermore, right choice of drugs is the key to treat clinical diseases.…”
Section: Introductionmentioning
confidence: 99%
“…P et ani mal acts as a crucial element in society where they perform important role in devel opment of children physically, mentally, and socially (Robertson et al, 2000), help the well-being of their owner to get play and exercise, help each other to compete with stress and in many countries, parents nursed pet animals as their child who have no child (Education and California State Polytechnic University, Pomona, CA, 2015). Among them dog is the principal one which play different significant roles, such as providing assistance to the blind and disabled person and sniffers dogs used by police and customs for improving activities of the defense section of the country to detect crime (Yadav et al, 2017). They are not only a companion animal but also acts as workers (Singh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%